Precarity and State Liberal Approach toward Indonesian Local Game Industry - Allifiansyah, Sandy; Nedpogaeo, Asawin (Future Science / FSH-PH Publications, 2022)
This paper aims to portrait the contemporary situation of Indonesian local game industry regarding the working-class issues and state approach to the development and sustainability. As Indonesian local game industry began a new era after state recognition in 2014, the industrial durability in the national creative sector is often questioned. A case study method is applied to response and diagnose one of the newest creative economic sectors in Indonesia. Interviewing various parties such as two related state ministries, twelve founders of local game studios, ten local game workers, and representative of labor union. The result exposes a liberal approach from the state in nurturing local game industry such as free-market competition, nescience, and quasi-patronage. This particular style of state’s cultural policy to local gaming industry has resulted in precarious situation among local game labors as the state’s instruments in contemporary creative industry.